Nomen est omen. Onimi kao sastavnice hrvatskih i engleskih frazema - Zoričić, Dunja (2019)
U ovome se članku kontrastivno analiziraju odabrani hrvatski i engleski frazemi leksičkog polja onima. Riječ je o frazemima kojima je sastavnicom vlastito ime, odnosno toponim, etnonim ili antroponim. Cilj je rada bio provesti kontrastivnu analizu navedenih frazema da bi se utvrdile podudarnosti, sličnosti i razlike hrvatske i engleske onimijske frazeologije. Također se u odnos stavljaju dvije kulture različite prošlosti i sociolingvističke pozadine, jedne anglosaksonske, druge slavenske. Polazište analize su hrvatski frazemi za koje se tražilo izrazne i/ili sadržajne ekvivalente. Kontrastivnom su analizom frazemi podijeljeni u tri skupine kroz koje se uočavaju njihove podudarnosti i različitosti, odnosno daje se pregled posebnosti dvaju frazeoloških fondova uvjetovanih kulturološkom, socijalnom, političkom, povijesnom ili nekom drugom značajkom.
In this paper we analyse Croatian and English phrasemes with an onymic component, which can either have a status of a toponym, an ethnonym, or an anthroponym. The aim of the paper is to determine the similarities and the differences between Croatian and English onymic phrasemes using contrastive analysis. Additionally, Croatian and English are observed as two spatially and genealogically distant languages. This is done in order to identify the differences and peculiarities conditioned by cultural, social, political, historical or some other features. This paper compares two cultures with different histories and sociolinguistic backgrounds, one Anglo-Saxon, the other Slavic. The analysis has shown that phrasemes with onymic components can be divided into three groups. The first group consists of corresponding Croatian and English onymic phrasemes, which means both phrasemes contain an identical proper name, lexically as well as structurally equal phrase, and the same motivation for the figurative meaning, i.e. background. The second group consists of phrasemes that contain an identical proper name but are partially different in phrase structure. The last group consists of Croatian and English phrasemes that share the same meaning, but differ in phrase structure, the onymic component, and background. The analysis has revealed that the third group was the largest (57,4%). It can be concluded that phrasemes with an onymic component represent not only human traits and life adventures, which are mostly metaphorically mirrored through the prism of historical, biblical, and mythological personalities or events, but that such phrasemes also complement and enrich phraseology of many languages, thus bringing together and strengthening the (shared) history of their nations ​​and cultures.
Bilješke uz tekst.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 138-140.
Sažetak ; Summary.
Keywords: Hrvatski jezik -- Engleski jezik -- Frazeologija -- Frazemi -- Kontrastivna analiza